Effectiveness of hybrid discarded tire/Industrial steel fibers for improving the sustainability of concrete structures. (16th May 2023) - Zia, Asad; Zhang, Pu; Holly, Ivan
Highlights: Experimental properties of concrete reinforced with hybrid steel fibers are investigated. The linear shrinkage, strength properties, ductility, and energy absorption are evaluated. The considered properties are significantly improved. The effectiveness of hybrid fibers for sustainable rigid pavements is studied. Hybrid fibers are more beneficial than using industrial or raw steel fibers separately. Abstract: Using waste and raw materials in construction materials is vital for sustainable construction. In this respect, the use of discarded tire steel fibers (DSFs) is encouraged in the construction industry to decrease pollution. On the other hand, the production of commonly used industrial steel fibers (ISFs) involves emissions of CO2 . Many studies have been conducted to evaluate the influence of discarded tire steel fibers (DSFs) on concrete. It is found that using DSFs in raw form could not improve the desired properties as ISFs do. Therefore, it is expected that using both ISFs and DSFs together can help achieve the desired improvements in concrete properties for various civil engineering applications. The main objective of the current investigation is the effective use of DSFs for developing eco-friendly, sustainable concrete. This study aims to evaluate the experimental properties of fiber-reinforced concrete, incorporating hybrid fibers (DSFs and ISFs together). Concrete specimens containing 0%, 0.50%, 0.60%, and 0.70% hybrid fibers by volume fraction are prepared. The hybrid fibers (HFs) comprise 30% of industrial steel fibers (ISFs) and 70% of discarded tire steel fibers (DSF) for each proportion. The 28th-day properties are examined. The slump and densities are determined. The experimental testing includes elastic modulus, compression (CS), split-tensile (SS), and bending testing (FS). The strength properties, deflection index, residual flexure strength, energy absorption, toughness index, and cracking behavior are reported. Moreover, the water absorption and linear shrinkage are also calculated. Except for the elastic modulus test, ASTM standards are used for casting and testing. A reduction of 45% in the LS and enhancements of 9.1%, 38%, 37%, and 23% are noticed in the EM, CS, SS, and FS of HFRC in contrast to zero-fiber concrete. Significant improvements are noticed in the properties of hybrid fiber-reinforced concrete compared to zero-fiber concrete.